ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) UNTUK MENINGKATKAN KEPUASAN PASIEN DI RSUD dr. RM. PRATOMO BAGANSIAPIAPI - Fery Indrawan; Adolf Bastian; Adi Rahmat (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving patient satisfaction at RSUD dr. RM. Pratomo Bagansiapiapi. The background of this research stems from the recognition that patient satisfaction is a key indicator of a hospital's success in delivering high-quality, user-oriented healthcare services. A qualitative descriptive method with a purposive sampling approach was employed. The informants consisted of the Hospital Director, Head of Medical Services, Head of Medical and Non-Medical Support Services, patients, and patients’ families. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that the implementation of TQM at the hospital has covered several essential elements, including customer focus, quality obsession, scientific approach, long-term commitment, teamwork, continuous improvement, education and training, controlled freedom, unity of purpose, and employee involvement and empowerment. However, challenges remain, such as limited resources, resistance to change, and suboptimal information management systems. These factors affect the overall level of patient satisfaction. The study affirms that TQM is not merely a managerial tool but a strategic framework that requires a collaborative and adaptive work culture. Strengthening managerial commitment, enhancing human resource capacity, and optimizing quality evaluation systems are crucial ongoing agendas to improve service quality and patient satisfaction comprehensively.Keywords: Total Quality Management (TQM), Service Quality, RSUD dr. RM. Pratomo Bagansiapiapi